Motif Waria Dalam Membangun Usaha Salon Kecantikan di Kecamatan Waru Sidoarjo - kartika sari, dwi ajeng; Listyani, Refti (Paradigma, 2023)
This research was conducted to find out about the in-depth motives of transgender women who decided to open a salon business in Waru Sidoarjo. This study uses a phenomenological approach from Alfred Schutz which explains events experienced by humans as life experiences in forming an awareness. This study uses Schutz's motive theory which has two indications of motive, namely because of motive and In Order Motive. The location of this research was carried out in the Waru area of Sidoarjo which was previously known for transgender prostitution. The subject of this research is a transgender who opens a beauty salon in the Waru district, Sidoarjo. The purpose of this research is to analyze and study how transgender motives are in opening a beauty salon business and to describe the overall motives. "waria" in bahasa is an abbreviation of female male, which means a man who looks like a woman in terms of character and appearance. In their daily lives, transgender people experience many obstacles in sosializing due to their differences with society because they have violated the nature of gifts from God and violated religious and sosial norms. Transgender experience conflicting identities psychologically so they will find it difficult to express their sexual needs because "waria" have withdrawn from gay and homo groups. Furthermore, this is what underlies transgender women in opening a beauty salon business so that they can create a better image for transgender both from an economic and societal perspective. Furthermore, the transgender will secretly find a date or partner by expanding relations by opening a salon business in the hope of finding new friends and getting a positive label for transgender as a goal.